Framing Berita Media Online Okezone.com Terhadap Munculnya Ganjar Pranowo dalam Tayangan Adzan Televisi - Afnan Iliya Tsabita; Sunaryanto (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
This study was conducted to interpret the news framing carried out by the online media Okezone.com regarding the appearance of Ganjar Pranowo in the Adzan television broadcast. This study is a qualitative type using Robert M. Entmant's media framing text analysis as an analytical tool consisting of. The conclusion of the study is the define problems, diagnose causes, make moral judgments, and treatment recommendations Okezone.com considers that the broadcast of Ganjar Pranowo's adzan on television is not part of identity politics. Okezone.com's framing of Ganjar Pranowo's side can be seen from the news titles exposed in the Okezone.com media and its contents which only report on people and parties who have a point of view that rejects the broadcast of Ganjar Pranowo's adzan as a form of identity politics and is included in campaign violations. Okezone invites the public to see Ganjar Pranowo's vision and vision and not on identity politics through the broadcast of the adzan. The broadcast of the call to prayer featuring Ganjar Pranowo is only a form of obedience of an ordinary citizen and not identity politics so it does not violate broadcasting regulations and campaign activities. The solution to the problem offered by Okezone.com is to invite the public to focus on the ideas of the presidential candidate rather than seeing identity politics in the broadcast of Ganjar Pranowo's call to prayer